When heaven calls : life lessons from America's top psychic medium - Fraser, Matt (Gallery Books, 2020)
"America's top psychic medium reflects on his life of speaking to Spirit and the lessons he's learned along the way-from both the living and the dead. People who are not in the habit of talking with the dead have a hard time imagining what Matt Fraser's life is like. Based on the questions he gets, they seem to think he spends most of his time sitting cross-legged in a trance, maybe hovering a few inches off the ground, leaving his physical body behind as he journeys across the veil to the spirit realm. But it's not like that at all. The real Matt Fraser is just an ordinary twenty-eight-year-old guy...who happens to talk to dead people. Born into a psychic family, Matt carries on the legacy passed down from his late Grandmother Mary by connecting people to their dearly departed loved ones and delivering messages from the other side. His sold-out live group readings, television appearances, and popular private readings have allowed him to bring hope and healing to fans from around the world. Now, in When Heaven Calls, Matt opens up about his life as a psychic medium-including how he discovered his spiritual gift, what it's like to connect with souls on the other side, what communicating with the dead has taught him about embracing life, and how you can tap into your own intuitive awareness to manifest your dreams, goals, and desires"--